Rhetorical and Miracle Textual Symbols in Sūra al-Raḥmān - Al Rashidi, Muhammad Ayub; Rehman, Badshah (Journal of Islamic and Religious Studies, 2016)
The term “Balãgha” is used in Arabic literature. The word Balagha is derived from a root “ بلغ” (Balãgha) meaning “ to reach” and the etymology is explained by interpreting the “Balãgha” as the art of reaching the listener in attempting to convey one`s idea to him, or the art of reaching the utmost perfection in the style and content of a composition. A perfect word for the term Balagha in English literature is Rhetoric. It is the body of principles and theory having to do with the presentation of facts and ideas in clear, convincing and attractive language. The traditional aim of rhetoric was to give effectiveness to public speech. Rhetoric is a comprehensive science just as much concerned with what one could say as how one might say it. It studies the effectiveness of language comprehensively including its emotional impact as well as its propositional content. The title of my paper reflects the rhetorical aspects of the Sūrah Al-Rahmān. It is a part of the Holy Quran.